2009
DOI: 10.1074/jbc.m900575200
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Assembly of Heteromeric γ-Aminobutyric Acid Type B Receptor Subunits in Hippocampal Neurons

Abstract: Understanding the mechanisms that control synaptic efficacy through the availability of neurotransmitter receptors depends on uncovering their specific intracellular trafficking routes. ␥-Aminobutyric acid type B (GABA B ) receptors (GABA B Rs) are obligatory heteromers present at dendritic excitatory and inhibitory postsynaptic sites. It is unknown whether synthesis and assembly of GABA B Rs occur in the somatic endoplasmic reticulum (ER) followed by vesicular transport to dendrites or whether somatic synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 47 publications
4
42
0
Order By: Relevance
“…Both the C-terminal domain of the GABA B1 and GABA B2 subunits contain a number of putative dendritic targeting signals. It was recently proposed that GABA B1 and GABA B2 subunits are transported into dendrites while still residing in the ER and before assembly into heteromeric complexes (Vidal et al, 2007;Ramírez et al, 2009). Consistent with this proposal, we found a colocalization of transfected GABA B1 protein with ER-targeted GFP.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Both the C-terminal domain of the GABA B1 and GABA B2 subunits contain a number of putative dendritic targeting signals. It was recently proposed that GABA B1 and GABA B2 subunits are transported into dendrites while still residing in the ER and before assembly into heteromeric complexes (Vidal et al, 2007;Ramírez et al, 2009). Consistent with this proposal, we found a colocalization of transfected GABA B1 protein with ER-targeted GFP.…”
Section: Discussionsupporting
confidence: 80%
“…It is therefore conceivable that GABA B1a traffics into axons within the ER. As previously reported (Ramírez et al, 2009), we found a partial colocalization of transfected GABA B1a subunits with the ER in the somatodendritic compartment using an ER-targeted GFP (Aoki et al, 2002) as a marker (supplemental Fig. S2, available at www.…”
Section: Resultssupporting
confidence: 56%
“…ACTL6B, encoding Actin-like 6B (also known as BAF53B), is a pivotal co-factor for the SWI/SNF neuron-specific chromatin remodeling complex nBAF, which is required for neural development and dendritic outgrowth. 27,28 Also, GABBR2, which is a component of the G proteincoupled GABA receptor, plays a critical role in the fine-tuning of inhibitory synaptic transmission, [29][30][31] and other members of the GABA receptor family have already been conclusively linked to neurodevelopmental disorders. 32,33 GABBR2 was very recently also reported by others to show significant de novo mutation clustering in a neurodevelopmental cohort.…”
mentioning
confidence: 99%
“…However, segregated GABA B1 and GABA B2 subunits are detected by light and electron microscopy in hippocampal and visual cortex neurons (Gonchar et al, 2001;Ramírez et al, 2009;Biermann et al, 2010). Because GABA B1 is exported from the ER only upon binding to GABA B2 this evidence suggests that they utilize an alternative ER transport pathway into dendrites during the early stages of their biosynthetic itinerary.…”
Section: Introductionmentioning
confidence: 98%